REKLAMASI KAWASAN TELUK PALU DITINJAU DARI ASPEK HUKUM TATA RUANG - Muliati, Muliati (Katalogis, 2015)
This research purpose is to know and analyze based on statutory provision regard due reclamation planning, permitting reclamation, and reclamation as well as to identify and analyze whether Palu Bay reclamation area in accordance with the Spatial Plan of Palu Year 2010-2030, with normative research and analyzed with descriptive methods. Research shown that the implementation of reclamation is accordance with legislation proceeds through the stages of planning , licence and reclamation . Related Palu Bay reclamation area , has not been fully fit Spatial Planning Palu as the setting in the Regional Regulation No. 16Â  Year 2011 about RTRW Palu City Year 2010-2030 .